2021
DOI: 10.1038/s41467-021-25111-7
|View full text |Cite
|
Sign up to set email alerts
|

Soft gamma rays from low accreting supermassive black holes and connection to energetic neutrinos

Abstract: The Universe is filled with a diffuse background of MeV gamma-rays and PeV neutrinos, whose origins are unknown. Here, we propose a scenario that can account for both backgrounds simultaneously. Low-luminosity active galactic nuclei have hot accretion flows where thermal electrons naturally emit soft gamma rays via Comptonization of their synchrotron photons. Protons there can be accelerated via turbulence or reconnection, producing high-energy neutrinos via hadronic interactions. We demonstrate that our model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 115 publications
0
17
0
Order By: Relevance
“…There has been significant progress in numerical simulations of particle acceleration in shocks and accretion flows [328][329][330], and in spark gaps [331,332]. Non-jetted AGN [333][334][335][336], TDEs [337][338][339], choked jets [340][341][342][343], and interacting supernovae [344,345] are actively discussed as promising targets for high-energy neutrino detection.…”
Section: In Astrophysicsmentioning
confidence: 99%

High-Energy and Ultra-High-Energy Neutrinos

Ackermann,
Agarwalla,
Alvarez-Muñiz
et al. 2022
Preprint
Self Cite
“…There has been significant progress in numerical simulations of particle acceleration in shocks and accretion flows [328][329][330], and in spark gaps [331,332]. Non-jetted AGN [333][334][335][336], TDEs [337][338][339], choked jets [340][341][342][343], and interacting supernovae [344,345] are actively discussed as promising targets for high-energy neutrino detection.…”
Section: In Astrophysicsmentioning
confidence: 99%

High-Energy and Ultra-High-Energy Neutrinos

Ackermann,
Agarwalla,
Alvarez-Muñiz
et al. 2022
Preprint
Self Cite
“…In this model, the same acceleration mechanism is expected to operate in RIAFs. 56,63,82 By applying similar physical parameters to RIAFs for particle acceleration (although the plasma β in RIAFs is expected to be larger), higher-energy neutrino data above 100 TeV can simultaneously be explained (see Figure 11). In this sense, AGN with different luminosities from LL AGN to luminous AGN including Seyfert galaxies and quasars can explain the all-sky neutrino intensity from a few TeV to a few PeV energies.…”
Section: Ws-rv961x669mentioning
confidence: 99%
“…Such a scenario was suggested by Stecker and Salamon 113 and Inoue et al 114 More recently, LL AGN have also been suggested as the sources of the MeV γ-ray background. 56 In this scenario, the MeV γ-ray background is attributed to Compton emission by thermal electrons in the hot RIAF plasma. To identify the sources and discriminate among different possibilities, both auto-correlation and cross-correlation searches are necessary, which will be feasible with future MeV γ-ray telescopes.…”
Section: Ws-rv961x669mentioning
confidence: 99%
See 2 more Smart Citations